CHEK2 Germline Variants in Cancer Predisposition: Stalemate Rather than Checkmate - Stolarova, Lenka; Kleiblova, Petra; Janatova, Marketa; Soukupova, Jana; Zemankova, Petra; Macurek, Libor; Kleibl, Zdenek (Cells, 2020)
Germline alterations in many genes coding for proteins regulating DNA repair and DNA damage response (DDR) to DNA double-strand breaks (DDSB) have been recognized as pathogenic factors in hereditary cancer predisposition. The ATM-CHEK2-p53 axis has been documented as a backbone for DDR and hypothesized as a barrier against cancer initiation. However, although CHK2 kinase coded by the CHEK2 gene expedites the DDR signal, its function in activation of p53-dependent cell cycle arrest is dispensable. CHEK2 mutations rank among the most frequent germline alterations revealed by germline genetic testing for various hereditary cancer predispositions, but their interpretation is not trivial. From the perspective of interpretation of germline CHEK2 variants, we review the current knowledge related to the structure of the CHEK2 gene, the function of CHK2 kinase, and the clinical significance of CHEK2 germline mutations in patients with hereditary breast, prostate, kidney, thyroid, and colon cancers.
Keywords: Checkpoint Kinase 2; breast cancer; zárodečné mutace; Genetic Predisposition to Disease; checkpoint kinasa 2; Neoplasms; checkpoint kinase 2; mutační rychlost; KAP1; Mutation Rate; germline mutation; prostate cancer; renal cancer; substrátová specifita; Germ-Line Mutation; Animals; lidé; CHEK2; CHK2; Humans; Substrate Specificity; zvířata; colorectal cancer; nádory; thyroid cancer; hereditary cancer; WIP1; genetická predispozice k nemoci